2007
DOI: 10.1016/j.bbr.2006.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of fear-, anxiety- and depression-related behavior across adolescence in C57BL/6J mice

Abstract: Adolescence is characterized by behavioral traits such as emotional lability and impulsivity that are associated with increased vulnerability to affective illness and addictions. Research in rodents has found that adolescent rats and mice differ from adults on measures of anxiety-like behavior, noveltyseeking and stress-responsivity. The present study sought to extend these data by evaluating fear-, anxiety-and depression-related behaviors in male C57BL/6J mice aged four (early adolescent), six (peri-adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
126
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(146 citation statements)
references
References 56 publications
20
126
0
Order By: Relevance
“…Indeed, 50-day-old rats are more attentive and display longer freezing, at a greater distance from the threat, than 20-day-old rats (Bronstein and Hirsch, 1976). In contrast, although 4-week-old mice exhibit more rapid and more robust acquisition of a conditioned association between an auditory stimulus and a foot shock compared with 6-8-week-old mice (Hefner and Holmes, 2007), other studies have shown that 4-week-old mice also display excessive generalization to auditory conditioned stimuli compared with 9-10-week-old mice . Altogether, these observations in mice suggest that aversive associations might be less specific in juveniles than in adults, and, although connectional refinement might occur in the amygdala during this late development , improvement of threat detection and defensive responses might also be linked to the maturation of other brain areas (e.g., prefrontal and sensory cortex) connected to the amygdala.…”
Section: Functional Considerationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, 50-day-old rats are more attentive and display longer freezing, at a greater distance from the threat, than 20-day-old rats (Bronstein and Hirsch, 1976). In contrast, although 4-week-old mice exhibit more rapid and more robust acquisition of a conditioned association between an auditory stimulus and a foot shock compared with 6-8-week-old mice (Hefner and Holmes, 2007), other studies have shown that 4-week-old mice also display excessive generalization to auditory conditioned stimuli compared with 9-10-week-old mice . Altogether, these observations in mice suggest that aversive associations might be less specific in juveniles than in adults, and, although connectional refinement might occur in the amygdala during this late development , improvement of threat detection and defensive responses might also be linked to the maturation of other brain areas (e.g., prefrontal and sensory cortex) connected to the amygdala.…”
Section: Functional Considerationsmentioning
confidence: 95%
“…Individual components of the fear response are thought to incorporate sequentially as animals mature, eventually giving rise to what are identified as mature fear behaviors (Wiedenmayer, 2009). Indeed, several studies have revealed that distinct fear behaviors emerge at different times during early postnatal life and continue to mature during late postnatal development (Blozovski and Cudennec, 1980;Bronstein and Hirsch, 1976;Chen et al, 2006;Collier et al, 1979;Foster and Burman, 2010;Hefner and Holmes, 2007;Hubbard et al, 2004;Ito et al, 2009;Kim and Richardson, 2007;Moriceau et al, 2004;Raineki et al, 2010;Rudy, 1993;Takahashi, 1992;Wiedenmayer andBarr, 1998, 2001a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The FST was conducted as previously described (Porsolt et al, 1978;Hefner and Holmes, 2007). The apparatus was a transparent Plexiglas cylinder (25 cm high, 20 cm diameter) filled halfway with water (24 ± 11C) into which the mouse was gently lowered for a 10 min trial.…”
Section: Depression-related Behavior and Glucocorticoid Responses To mentioning
confidence: 99%
“…After inhalation exposure, the first 5 minutes produced highest activity in mice as a result of the fear and stress emotionally from researcher's handling, inhalation device and test process. Hyperactive response induced from stress and fear are consistent with some researchers (Hefner & Holmes, 2007;Strekalova, Spanagel, Dolgov, & Bartsch, 2005 Administration with 50N caused a significant increase (* p<0.05) in the locomotion activity at 15 minutes after inhalation exposure, but no significant differences were observed afterwards. This is mostly possible due to short half-life(t1 2 ⁄ ) of nicotine in mice body.…”
Section: Assessment Of Viabilitiy Of Inhalation Of Nano-nicotine Via supporting
confidence: 91%